A MOFs / polyimide coating and a preparation method and application thereof

CN123004264APending Publication Date: 2026-10-30LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611226595.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-13
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

此类涂层在传统机油充分润滑条件下可提供良好的减摩抗磨效果,但其树脂基体的分子结构中含有羟基、醚键、酰胺键等极性基团,在甲酸、甲醇等介质中易发生溶胀、酯化或降解反应,导致涂层力学性能衰退、表面疏松,最终引发剥落乃至失效

Benefits of technology

[0016]本发明提供了上述方案所述MOFs/聚酰亚胺涂层或上述方案所述制备方法制备得到的MOFs/聚酰亚胺涂层在甲醇内燃机活塞裙部中的应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123004264A_ABST
    Figure CN123004264A_ABST
Patent Text Reader

Abstract

The application provides a MOFs / polyimide coating and a preparation method and application thereof, and belongs to the technical field of lubricating coating. Through the synergistic design of a PI corrosion-resistant base body and MOFs active filler, a solid-liquid composite lubricating system suitable for a methanol internal combustion engine piston skirt is constructed, balance between chemical corrosion resistance and low-temperature friction reduction and wear resistance is achieved, the limitation of the friction pair material design under alternating working conditions such as fluid lubrication, mixed lubrication, boundary lubrication, lean oil and dry friction is solved, and key material support is provided for long service life and high reliability operation of key moving parts such as the methanol engine piston skirt and the crankshaft bearing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lubrication coating technology, and more particularly to a MOFs / polyimide coating, its preparation method, and its application. Background Technology

[0002] With the deepening of the "dual-carbon" strategy and the transformation of the energy structure, alternative low-carbon fuels, represented by methanol, are being used more and more widely in the field of internal combustion engines. Methanol fuel is widely available, burns cleanly, and has low carbon emissions, and is considered one of the important technological paths to achieve green and low-carbon operation of internal combustion engines.

[0003] In critical moving components of an engine, an extremely thin oil film gap is maintained between the piston skirt and the cylinder liner. The anti-friction coating applied to its surface plays a crucial role in reducing frictional power consumption, preventing cylinder scoring and seizure, and ensuring long-term reliable engine operation. However, the actual service environment of a methanol internal combustion engine differs fundamentally from that of a traditional gasoline / diesel engine. The piston skirt coating faces the severe challenge of a combination of low mechanical load and strong chemical corrosion, posing new and urgent requirements for existing coating technologies.

[0004] Specifically, the high latent heat of methanol vaporization leads to a significantly lower skirt temperature during the cold start phase. The formic acid and formaldehyde byproducts generated from methanol combustion are highly corrosive, and unburned methanol easily seeps into the crankcase, diluting the lubricating oil and causing a sharp drop in oil film strength. This results in the coating frequently operating under boundary lubrication or even dry friction conditions. Existing piston skirt friction-reducing coatings are mostly composed of epoxy resin, phenolic resin, or polyamide-imide resin as the matrix, compounded with solid lubricants such as graphite, molybdenum disulfide, and carbon fiber. While these coatings can provide good friction reduction and anti-wear effects under conditions of sufficient lubrication with traditional engine oil, the molecular structure of their resin matrix contains polar groups such as hydroxyl, ether, and amide bonds. These groups are prone to swelling, esterification, or degradation reactions in media such as formic acid and methanol, leading to a decline in the coating's mechanical properties, surface porosity, and ultimately, peeling or failure.

[0005] Therefore, developing novel piston skirt coating materials that combine excellent formic acid corrosion resistance with reliable low-temperature friction reduction and wear resistance has become a key technological bottleneck that urgently needs to be overcome in the engineering application of methanol internal combustion engines. Summary of the Invention

[0006] In view of this, the purpose of this invention is to provide a MOFs / polyimide coating, its preparation method, and its application. The coating prepared by this invention has excellent resistance to formic acid and methanol corrosion, as well as excellent low-temperature friction reduction and wear resistance.

[0007] To achieve the above-mentioned objectives, the present invention provides the following technical solution: The present invention provides a MOFs / polyimide coating comprising a polyimide matrix and MOFs fillers dispersed in the polyimide matrix; wherein the polyimide matrix is ​​obtained by polycondensation and imidization reaction of aromatic diamine and aromatic dianhydride.

[0008] Preferably, the MOFs filler includes one or more of ZIF-8, NEHZIK, and MOF-5.

[0009] Preferably, the mass of the MOFs filler is 1 to 5% of the mass of the polyimide matrix.

[0010] Preferably, the aromatic diamine includes at least one of 3,4'-diaminodiphenyl ether and 4,4'-diaminodiphenyl ether; The aromatic dianhydride includes at least one of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, hexafluorodianhydride, and 4,4'-oxobisphthalic anhydride.

[0011] This invention provides a method for preparing the MOFs / polyimide coating described above, comprising the following steps: MOF fillers, aromatic diamines, aromatic dianhydrides and polar organic solvents are mixed and subjected to a polycondensation reaction to obtain a polyamic acid solution. The polyamic acid solution is mixed with a low-temperature imidization catalyst, and the resulting mixture is coated onto the substrate surface for imidization to obtain the MOFs / polyimide coating.

[0012] Preferably, by mass parts, the MOFs filler is 1 to 5 parts, the aromatic diamine is 15 to 40 parts, and the aromatic dianhydride is 30 to 80 parts.

[0013] Preferably, the low-temperature imidization catalyst includes one or more of quinoline, isoquinoline, and N-methylimidazole.

[0014] Preferably, the polar organic solvent includes one or more of N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide.

[0015] Preferably, the imidization process is as follows: sequentially heat treatment at 40~60℃ for 3 h, at 80~100℃ for 2 h, at 120~140℃ for 1 h, and at 160~200℃ for 1 h.

[0016] This invention provides the application of the MOFs / polyimide coating described in the above-described scheme or the MOFs / polyimide coating prepared by the preparation method described in the above-described scheme in the piston skirt of a methanol internal combustion engine.

[0017] To address the severe corrosion of piston skirt coatings by methanol combustion byproducts, this invention selects aromatic polyimide (PI), a resin matrix with excellent chemical inertness. Compared to epoxy, phenolic, and polyamide-imide resins, aromatic PI molecules do not contain hydroxyl groups, aliphatic ethers, or other active sites susceptible to formic acid attack. Its aromatic heterocyclic skeleton imparts extremely high chemical stability, resulting in significantly better formic acid corrosion resistance than the aforementioned resins. However, pure PI coatings still suffer from high friction coefficients and significant wear rates under harsh operating conditions, making it difficult to meet the requirements for long equipment lifespan and high reliability. To overcome this deficiency, introducing functional fillers is an effective strategy to improve the tribological properties of PI. However, the inert surfaces of traditional fillers (such as graphite, molybdenum disulfide, and carbon fiber) make it difficult for them to form strong interfacial bonds with the PI matrix, leading to debonding failure under cyclic shearing and subsequent performance degradation. This invention introduces MOFs as functional fillers. MOFs have the characteristics of ultra-high specific surface area, controllable structural dissociation and high reactivity. They can form strong interfacial bonds with the PI matrix through mechanical interlocking and chemical bonding. At the same time, during the friction process, a dense transfer film is generated on the surface of the metal pair through tribochemical reaction, which transforms the direct contact between the friction pairs into a low-shear interface between the coating / transfer film, thereby effectively reducing the friction coefficient and inhibiting wear failure.

[0018] By synergistically designing a PI corrosion-resistant matrix and MOFs active fillers, this invention constructs a solid-liquid composite lubrication system suitable for piston skirts in methanol internal combustion engines. It achieves a balance between chemical corrosion resistance and low-temperature friction reduction and wear resistance, solving the limitations on friction pair material design under alternating operating conditions such as fluid lubrication, mixed lubrication, boundary lubrication, lean oil, and dry friction. This provides key material support for the long-life and high-reliability operation of critical moving parts such as piston skirts and crankshaft bearings in methanol engines. Attached Figure Description

[0019] Figure 1 The images are scanning electron microscope images of the wear surfaces of the friction materials in Examples 1-3 and Comparative Examples 1-2, wherein (1) bearing steel; (2) PI coating; (3) ZIF-8 / PI coating; (4) NEHZIK / PI coating; and (5) MOF-5 / PI coating. Figure 2 The images are scanning electron microscope images of the transfer film surfaces of Examples 1-3 and Comparative Examples 1-2, wherein (1) bearing steel; (2) PI coating; (3) ZIF-8 / PI coating; (4) NEHZIK / PI coating; and (5) MOF-5 / PI coating. Figure 3 The graph shows the evolution trend of the friction coefficient of the friction materials in Examples 1-3 and Comparative Examples 1-2. Detailed Implementation

[0020] The present invention provides a MOFs / polyimide coating comprising a polyimide matrix and MOFs fillers dispersed in the polyimide matrix; wherein the polyimide matrix is ​​obtained by polycondensation and imidization reaction of aromatic diamine and aromatic dianhydride.

[0021] In this invention, the MOFs filler preferably includes one or more of ZIF-8, NEHZIK and MOF-5; the mass of the MOFs filler is preferably 1 to 5% of the mass of the polyimide matrix, and in specific embodiments it can be 1%, 2%, 3%, 4% or 5%.

[0022] In this invention, the aromatic diamine preferably includes at least one of 3,4'-diaminodiphenyl ether and 4,4'-diaminodiphenyl ether (ODA); the aromatic dianhydride includes at least one of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride (BPDA), hexafluorodianhydride (6FDA), and 4,4'-oxobisphthalic anhydride.

[0023] Compared to epoxy resins, phenolic resins, and PAI, aromatic PI molecules have a rigid heterocyclic backbone and do not contain active sites such as hydroxyl groups, aliphatic ethers, or amide bonds that are susceptible to formic acid attack. Their extremely high chemical inertness endows the coating with excellent resistance to formic acid and methanol corrosion. Furthermore, PI can act as a solid lubricant, providing friction reduction and anti-wear properties even under conditions of insufficient oil film.

[0024] However, pure PI coatings still suffer from high friction coefficients and significant wear rates under harsh operating conditions. To overcome this deficiency, introducing functional fillers is an effective strategy to improve the tribological properties of PI. However, the inert surfaces of traditional fillers (such as graphite, molybdenum disulfide, and carbon fiber) make it difficult for them to form strong interfacial bonds with the PI matrix, leading to debonding failure under cyclic shearing and resulting in performance degradation. This invention introduces MOFs as functional fillers. MOFs possess ultra-high specific surface area, controllable structural dissociation, and high reactivity, enabling them to form strong interfacial bonds with the PI matrix through mechanical interlocking and chemical bonding. Simultaneously, during friction, a dense transfer film can be generated on the metal-pair surface through tribochemical reactions, transforming the direct contact between the friction pairs into a low-shear interface between the coating and the transfer film, thereby effectively reducing the friction coefficient and suppressing wear failure.

[0025] In this invention, the thickness of the MOFs / polyimide coating is preferably 70~90μm, and in specific embodiments it can be 70, 75, 80, 85 or 90μm.

[0026] This invention provides a method for preparing the MOFs / polyimide coating described above, comprising the following steps: MOF fillers, aromatic diamines, aromatic dianhydrides and polar organic solvents are mixed and subjected to a polycondensation reaction to obtain a polyamic acid solution. The polyamic acid solution is mixed with a low-temperature imidization catalyst, and the resulting mixture is coated onto the substrate surface for imidization to obtain the MOFs / polyimide coating.

[0027] In this invention, the MOFs packing preferably includes one or more of ZIF-8, NEHZIK and MOF-5; the MOFs packing is prepared using methods well known in the art.

[0028] In this invention, the preferred method for preparing ZIF-8 includes the following steps: 5.0–10.0 parts by mass of 2-methylimidazole and 9.0–18.0 parts by mass of zinc salt are dissolved in 618.7 parts by mass of methanol to obtain a 2-methylimidazole solution and a zinc salt solution; under ultrasonic dispersion conditions, the 2-methylimidazole solution is dropped into the zinc salt solution and ultrasonically dispersed for 1–90 min; subsequently, the solution is placed in a 30°C water bath and allowed to stand for 12–36 h; the product is then washed by centrifugation with methanol and dried at 100°C to obtain white ZIF-8 powder. In this invention, the zinc salt is preferably at least one of zinc nitrate hexahydrate and zinc acetate dihydrate.

[0029] In this invention, the preferred method for preparing NEHZIK (diamond-like metallo-form alloys) includes the following steps: dissolving 50-100 parts by mass of zinc salt in 1560 parts by mass of deionized water to obtain a zinc salt solution; dispersing 20-50 parts by mass of uric acid in a 1023:265 (ethanol:water) mixture to obtain a dispersion; adding the zinc salt solution dropwise to the dispersion under magnetic stirring and a temperature of 0-40°C, while simultaneously starting an ultrasonic reactor for 30-120 min; washing the product by centrifugation with hot water, ethanol, and ether, and drying at room temperature to obtain white NEHZIK powder.

[0030] In this invention, the preferred method for preparing MOF-5 includes the following steps: dissolving 300-350 parts by mass of zinc salt and 70-80 parts by mass of terephthalic acid in 2000-2500 parts by mass of NMP, turning on the ultrasonic reactor, and continuing to sonicate for 5-30 min after a precipitate appears in the solution. The resulting product is washed by centrifugation with ethanol and dried at 100°C to obtain white MOF-5 powder.

[0031] This invention involves mixing MOF fillers, aromatic diamines, aromatic dianhydrides, and polar organic solvents to carry out a polycondensation reaction, thereby obtaining a polyamic acid (PAA) solution.

[0032] Based on mass parts, the MOFs filler is preferably 1-5 parts, and in specific embodiments, it can be 1, 2, 3, 4, or 5 parts; the aromatic diamine is preferably 15-40 parts, and in specific embodiments, it can be 15, 18, 20, 25, 28, 30.5, 35, 38, or 40 parts; the aromatic dianhydride is preferably 30-80 parts, and in specific embodiments, it can be 30, 40, 50, 60, 65, 67.3, 70, 75, or 80 parts; the polar organic solvent is preferably 400-900 parts, and in specific embodiments, it can be 400, 500, 600, 700, 756.4, 800, or 900 parts. In this invention, the polar organic solvent preferably includes one or more of N-methylpyrrolidone (NMP), N,N-dimethylformamide, and N,N-dimethylacetamide.

[0033] In this invention, the mixing preferably includes: dissolving an aromatic diamine in a polar organic solvent, and then adding MOF filler and aromatic dianhydride to the resulting solution.

[0034] In this invention, the temperature of the polycondensation reaction is preferably room temperature (i.e., no additional heating or cooling is required), and the reaction time is preferably 6 to 36 hours, which can be 6, 12, 18, 24, 28, 30, 32, or 36 hours in specific embodiments. In this invention, the polycondensation reaction is preferably carried out under a protective atmosphere; the protective atmosphere is preferably a nitrogen atmosphere or an argon atmosphere; and the polycondensation reaction is preferably carried out under stirring conditions. The stirring speed is preferably 30 to 160 rpm, which can be 30, 60, 90, 120, 140, or 160 rpm in specific embodiments.

[0035] After obtaining the polyamic acid solution, the present invention mixes the polyamic acid solution with a low-temperature imidization catalyst, coats the resulting mixture onto the substrate surface, and performs imidization to obtain the MOFs / polyimide coating.

[0036] In this invention, the low-temperature imidization catalyst preferably comprises one or more of quinoline, isoquinoline, and N-methylimidazole; based on the unit mass parts of the aromatic diamine, the amount of the low-temperature imidization catalyst is preferably 10-20 parts, and in specific embodiments it can be 10, 13, 15, 17, 18, 19.5, or 20 parts. The function of the low-temperature imidization catalyst is to lower the thermosetting temperature of polyimide (the temperature of conventional polyimide catalysts is 300-320℃). In the system, quinoline does not graft onto the resin matrix and volatilizes as the temperature rises during thermosetting.

[0037] In this invention, a low-temperature imidization catalyst is preferably added to the polyamic acid solution to achieve mixing. After adding the low-temperature imidization catalyst, the mixture is preferably stirred for 0.5 to 2 hours.

[0038] The present invention does not impose any special limitation on the coating method, which may specifically be drop coating, spray coating or spin coating.

[0039] This invention does not have special requirements for the substrate; the appropriate substrate can be selected according to the application scenario. In an embodiment of this invention, the substrate is GCr15 bearing steel.

[0040] In this invention, the imidization process is preferably: sequentially holding at 40~60℃ for 3 h, 80~100℃ for 2 h, 120~140℃ for 1 h, and 160~200℃ for 1 h; more preferably, sequentially holding at 50℃ for 3 h, 90℃ for 2 h, 120℃ for 1 h, and 180℃ for 1 h.

[0041] This invention provides the application of the MOFs / polyimide coating described in the above-described scheme or the MOFs / polyimide coating prepared by the preparation method described in the above-described scheme in the piston skirt of a methanol internal combustion engine.

[0042] The following detailed description of the MOFs / polyimide coating, its preparation method, and its application provided by the present invention, with reference to specific examples, should not be construed as limiting the scope of protection of the present invention.

[0043] Example 1 Synthesis of ZIF-8: 7.7 parts of 2-methylimidazole and 13.9 parts of Zn(NO3)2·6H2O were dissolved in 618.7 parts of methanol, respectively. Under ultrasonic dispersion conditions in an ultrasonic cleaner, the 2-methylimidazole solution was added dropwise to the Zn(NO3)2·6H2O solution, and sonicated for 30 min. The mixture was then placed in a 30℃ water bath and allowed to stand for 24 h. The product was washed by centrifugation with methanol and dried at 100℃ to obtain white ZIF-8 powder.

[0044] Preparation of ZIF-8 / PI coating: 756.4 parts NMP, 19.5 parts quinoline, 30.3 parts ODA, 3.0 parts ZIF-8, and 67.3 parts 6FDA were weighed. NMP and ODA were added to a three-necked flask, and after the ODA was completely dissolved, ZIF-8 and 6FDA were added. The reaction was carried out under a nitrogen atmosphere and mechanical stirring at 60 rpm for 24 h to obtain a PAA solution. Quinoline was then added to the system, and after stirring for 1 h, it was uniformly drop-coated onto the surface of a GCr15 bearing steel substrate. The substrate was then placed in a vacuum oven for imidization using a programmed temperature rise: 50℃-3 h, 90℃-2 h, 120℃-1 h, and 180℃-1 h. After cooling to room temperature, the friction test coating material was obtained.

[0045] Tribological performance testing was conducted in accordance with ASTM G99-2017, using a ball-disc contact mode. The test conditions were 16 N, 0.1 m / s, with PAO-6 base oil as the lubricant. The upper sample was a 5 mm GCr15 bearing steel ball, and the test temperature was 20~25℃.

[0046] Example 2 Synthesis of NEHZIK: 92.9 parts Zn(NO3)2·6H2O were dissolved in 1560 parts deionized water, and 43.1 parts uric acid were dispersed in a 1023:265 (ethanol:water) mixture. Under magnetic stirring and at 0°C, the Zn(NO3)2·6H2O solution was added dropwise to the dispersion at a rate of 4 mL / min, while simultaneously reacting in an ultrasonic reactor for 60 min. The product was washed by centrifugation with hot water, ethanol, and diethyl ether, and dried at room temperature to obtain a white powder.

[0047] Preparation of NEHZIK / PI coating: 756.4 parts NMP, 19.5 parts quinoline, 30.3 parts ODA, 3.0 parts NEHZIK, and 67.3 parts 6FDA were weighed. NMP and ODA were added to a three-necked flask, and after the ODA was completely dissolved, NEHZIK and 6FDA were added. The reaction was carried out under a nitrogen atmosphere and mechanical stirring at 60 rpm for 24 h to obtain a PAA solution. Quinoline was then added to the system, and after stirring for 1 h, it was uniformly drop-coated onto the surface of a GCr15 bearing steel substrate. The substrate was then placed in a vacuum oven for imidization using a programmed temperature rise: 50℃-3 h, 90℃-2 h, 120℃-1 h, and 180℃-1 h. After cooling to room temperature, the friction test coating material was obtained.

[0048] Tribological performance testing was conducted in accordance with ASTM G99-2017, using a ball-disc contact mode. The test conditions were 16 N, 0.1 m / s, with PAO-6 base oil as the lubricant. The upper sample was a 5 mm GCr15 bearing steel ball, and the test temperature was 20~25℃.

[0049] Example 3 Synthesis of MOF-5: 326.6 parts of zinc salt and 78.3 parts of terephthalic acid were dissolved in 2000~2500 parts of NMP. The ultrasonic reactor was turned on, and after the precipitate appeared in the solution, the ultrasonication was continued for 10 min. The product was washed by centrifugation with ethanol and dried at 100℃ to obtain white powder MOF-5.

[0050] Preparation of MOF-5 / PI coating: 756.4 parts NMP, 19.5 parts quinoline, 30.3 parts ODA, 3.0 parts MOF-5, and 67.3 parts 6FDA were weighed. NMP and ODA were added to a 250 mL three-necked flask. After the ODA was completely dissolved, MOF-5 and 6FDA were added. The reaction was carried out under a nitrogen atmosphere and mechanical stirring at 60 rpm for 24 h to obtain a PAA solution. Quinoline was then added to the system, and after stirring for 1 h, it was uniformly drop-coated onto the surface of a GCr15 bearing steel substrate. The substrate was then placed in a vacuum oven for imidization using a programmed temperature rise: 50℃-3 h, 90℃-2 h, 120℃-1 h, and 180℃-1 h. After cooling to room temperature, the friction test coating material was obtained.

[0051] Tribological performance testing was conducted in accordance with ASTM G99-2017, using a ball-disc contact mode. The test conditions were 16 N, 0.1 m / s, with PAO-6 base oil as the lubricant. The upper sample was a 5 mm GCr15 bearing steel ball, and the test temperature was 20~25℃.

[0052] Comparative Example 1 (Uncoated): Tribological performance testing was conducted in accordance with ASTM G99-2017, using a ball-disc contact mode. The test conditions were 16 N, 0.1 m / s, with PAO-6 base oil as the lubricant. The upper sample was a 5 mm GCr15 bearing steel ball, and the lower sample was a GCr15 bearing steel disc. The test temperature was 20~25℃.

[0053] Comparative Example 2 (pure PI coating, lubricating medium is PAO-6 base oil): Preparation of PI coating: 756.4 parts NMP, 20 parts quinoline, 31.3 parts ODA, and 69.4 parts 6FDA were weighed. NMP and ODA were added to a three-necked flask, and 6FDA was added after the ODA was completely dissolved. The mixture was reacted for 24 hours under a nitrogen atmosphere and mechanical stirring at 60 rpm to obtain a PAA solution. Quinoline was then added to the system, and after stirring for 1 hour, it was uniformly drop-coated onto the surface of a GCr15 bearing steel substrate. The substrate was then placed in a vacuum oven for imidization using a programmed temperature rise: 50℃-3 h, 90℃-2 h, 120℃-1 h, and 180℃-1 h. After cooling to room temperature, the friction test coating material was obtained.

[0054] Tribological performance testing was conducted in accordance with ASTM G99-2017, using a ball-disc contact mode. The test conditions were 16 N, 0.1 m / s, with PAO-6 base oil as the lubricant. The upper sample was a 5 mm GCr15 bearing steel ball, and the test temperature was 20~25℃.

[0055] Comparative Example 3 (Gr / PI coating) Preparation of Gr / PI coating: 756.4 parts NMP, 19.5 parts quinoline, 30.3 parts ODA, 3 parts graphite (Gr), and 67.3 parts 6FDA were weighed. NMP and ODA were added to a three-necked flask, and after the ODA was completely dissolved, Gr and 6FDA were added. The reaction was carried out under a nitrogen atmosphere and mechanical stirring at 60 rpm for 24 h to obtain a PAA solution. Quinoline was then added to the system, and after stirring for 1 h, it was uniformly drop-coated onto the surface of a GCr15 bearing steel substrate. The substrate was then placed in a vacuum oven for imidization using a programmed temperature rise: 50℃-3 h, 90℃-2 h, 120℃-1 h, and 180℃-1 h. After cooling to room temperature, the friction test coating material was obtained.

[0056] Tribological performance testing was conducted in accordance with ASTM G99-2017, using a ball-disc contact mode. The test conditions were 16 N, 0.1 m / s, with PAO-6 base oil as the lubricant. The upper sample was a 5 mm GCr15 bearing steel ball, and the test temperature was 20~25℃.

[0057] Comparative Example 4 (MoS2 / PI coating) Preparation of MoS2 / PI coating: 756.4 parts NMP, 19.5 parts quinoline, 30.3 parts ODA, 3 parts molybdenum disulfide (MoS2), and 67.3 parts 6FDA were weighed. NMP and ODA were added to a three-necked flask, and after the ODA was completely dissolved, MoS2 and 6FDA were added. The reaction was carried out under a nitrogen atmosphere and mechanical stirring at 60 rpm for 24 h to obtain a PAA solution. Quinoline was then added to the system, and after stirring for 1 h, it was uniformly drop-coated onto the surface of a GCr15 bearing steel substrate. The substrate was then placed in a vacuum oven for imidization using a programmed temperature rise: 50℃-3 h, 90℃-2 h, 120℃-1 h, and 180℃-1 h. After cooling to room temperature, the friction test coating material was obtained.

[0058] Tribological performance testing was conducted in accordance with ASTM G99-2017, using a ball-disc contact mode. The test conditions were 16 N, 0.1 m / s, with PAO-6 base oil as the lubricant. The upper sample was a 5 mm GCr15 bearing steel ball, and the test temperature was 20~25℃.

[0059] Comparative Example 5 (CFs / PI coating) Preparation of CFs / PI coating: 756.4 parts NMP, 19.5 parts quinoline, 30.3 parts ODA, 3 parts carbon fiber (CFs), and 67.3 parts 6FDA were weighed. NMP and ODA were added to a 250 mL three-necked flask. After the ODA was completely dissolved, CFs and 6FDA were added. The reaction was carried out under a nitrogen atmosphere and mechanical stirring at 60 rpm for 24 h to obtain a PAA solution. Quinoline was then added to the system, and after stirring for 1 h, it was uniformly drop-coated onto the surface of a GCr15 bearing steel substrate. The substrate was then placed in a vacuum oven for imidization using a programmed temperature rise: 50℃-3 h, 90℃-2 h, 120℃-1 h, and 180℃-1 h. After cooling to room temperature, the friction test coating material was obtained.

[0060] Tribological performance testing was conducted in accordance with ASTM G99-2017, using a ball-disc contact mode. The test conditions were 16 N, 0.1 m / s, with PAO-6 base oil as the lubricant. The upper sample was a 5 mm GCr15 bearing steel ball, and the test temperature was 20~25℃.

[0061] Comparative Examples 6-8 (pure PI coating, lubricating medium is MOFs / PAO-6 lubricating oil): Synthesis of MOFs / PAO-6 lubricating oil: Using PAO-6 as the base oil, ZIF-8, NEHZIK, and MOF-5 were each added in a 3-part ratio to 32.3 parts of PAO-6 base oil. The MOFs / PAO-6 lubricating oil was pre-dispersed by magnetic stirring for 30 min, followed by ultrasonic dispersion for 30 min to ensure uniform dispersion of MOFs in the PAO-6 base oil.

[0062] Preparation of PI coating: 756.4 parts NMP, 20 parts quinoline, 31.3 parts ODA, and 69.4 parts 6FDA were weighed. NMP and ODA were added to a three-necked flask, and 6FDA was added after the ODA was completely dissolved. The reaction was carried out under a nitrogen atmosphere and mechanical stirring at 60 rpm for 24 h to obtain a PAA solution. Quinoline was then added to the system, and after stirring for 1 h, it was uniformly drop-coated onto the surface of a GCr15 bearing steel substrate. The substrate was then placed in a vacuum oven for imidization using a programmed temperature rise: 50℃-3 h, 90℃-2 h, 120℃-1 h, and 180℃-1 h. After cooling to room temperature, the friction test coating material was obtained.

[0063] Tribological performance testing was conducted in accordance with ASTM G99-2017, using a ball-disc contact mode. The test conditions were 16 N, 0.1 m / s, with MOFs / PAO-6 lubricating oil as the lubricating medium. The upper sample was a 5 mm GCr15 bearing steel ball, and the test temperature was 20~25℃.

[0064] The tribological performance test results of Examples 1-3 and Comparative Examples 1-8 are summarized in Table 1.

[0065] Table 1. Tribological properties of Examples 1-3 and Comparative Examples 1-8

[0066] As shown in Table 1, the MOFs / polyimide composite coatings prepared in Examples 1-3 of this invention exhibit superior friction-reducing and wear-resistant properties compared to Comparative Examples 1-8. Under uncoated conditions, the friction coefficient and wear rate of the oil-lubricated system are both high; the tribological properties of the material are significantly improved after the introduction of the PI coating. Although the introduction of traditional fillers can further improve the tribological properties of the system, the reinforcing effect is limited due to the weak interfacial bonding between the filler and the matrix. In contrast, the introduction of MOFs significantly strengthens the interfacial bonding through the synergistic effect of mechanical interlocking and chemical bonding, thereby greatly improving the tribological properties; however, when MOFs are used as lubricant additives, their performance improvement effect is still not as good as that of the MOFs / PI composite coating.

[0067] Scanning electron microscopy was performed on the worn surfaces of the friction materials in Examples 1-3 and Comparative Examples 1-2. The results are as follows: Figure 1 As shown, (1) bearing steel; (2) PI coating; (3) ZIF-8 / PI coating; (4) NEHZIK / PI coating; (5) MOF-5 / PI coating. (The text appears to be incomplete and requires further context.) Figure 1 It is evident that under oil lubrication conditions, the bearing steel surface exhibits a distinct ploughing morphology, primarily attributed to severe three-body abrasive wear induced by hard abrasive debris. Introducing a solid lubricant coating reduces three-body abrasive wear, but fatigue fracture characteristics are still observed. The pure PI coating exhibits severe fatigue wear, while introducing MOFs into the PI matrix increases the coating's hardness and significantly reduces fatigue wear.

[0068] Scanning electron microscopy was performed on the surface of the transfer films of Examples 1-3 and Comparative Examples 1-2, and the results are as follows: Figure 2 As shown, (1) bearing steel; (2) PI coating; (3) ZIF-8 / PI coating; (4) NEHZIK / PI coating; (5) MOF-5 / PI coating. (The text appears to be incomplete and requires further context.) Figure 2 It is evident that in oil-lubricated systems, direct contact between micro-protrusions leads to severe wear on the surfaces of the mating steel balls. A sparsely distributed friction film can be observed on the mating surface of the pure PI coating. After introducing MOFs, the surface smoothness of the three MOFs / PI composite coatings is significantly improved, and the friction film coverage area is markedly increased. This indicates that the three materials not only effectively protect the mating steel balls but also reduce their own wear rate by forming a high-coverage friction film.

[0069] Figure 3The evolution trend of the friction coefficient of the friction materials in Examples 1-3 and Comparative Examples 1-2 is shown. The oil-lubricated system has a running-in time of up to 800 s, and the friction coefficient curve still shows slight fluctuations after entering the frictional stability stage. After introducing coatings on the bearing steel surface, the friction coefficient of the ZIF-8 / PI and NEHZIK / PI composite coatings decreased to about 0.05, the running-in time was shortened to 300 s, and the friction interface stability was the best. The running-in time of the MOF-5 / PI composite coating was 500 s, but it still maintained high frictional stability.

[0070] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A MOFs / polyimide coating, characterized in that, It includes a polyimide matrix and MOFs fillers dispersed in the polyimide matrix; the polyimide matrix is ​​obtained by polycondensation and imidization reaction of aromatic diamine and aromatic dianhydride.

2. The preparation method according to claim 1, characterized in that, The MOFs packing includes one or more of ZIF-8, NEHZIK, and MOF-5.

3. The preparation method according to claim 1, characterized in that, The mass of the MOF filler is 1 to 5% of the mass of the polyimide matrix.

4. The preparation method according to claim 1, characterized in that, The aromatic diamine includes at least one of 3,4'-diaminodiphenyl ether and 4,4'-diaminodiphenyl ether; The aromatic dianhydride includes at least one of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, hexafluorodianhydride, and 4,4'-oxobisphthalic anhydride.

5. The method for preparing the MOFs / polyimide coating according to any one of claims 1 to 4, characterized in that, Includes the following steps: MOF fillers, aromatic diamines, aromatic dianhydrides and polar organic solvents are mixed and subjected to a polycondensation reaction to obtain a polyamic acid solution. The polyamic acid solution is mixed with a low-temperature imidization catalyst, and the resulting mixture is coated onto the substrate surface for imidization to obtain the MOFs / polyimide coating.

6. The preparation method according to claim 1, characterized in that, By mass fraction, the MOFs filler is 1-5 parts, the aromatic diamine is 15-40 parts, and the aromatic dianhydride is 30-80 parts.

7. The preparation method according to claim 1, characterized in that, The low-temperature imidization catalyst includes one or more of quinoline, isoquinoline, and N-methylimidazole.

8. The preparation method according to claim 1, characterized in that, The polar organic solvent includes one or more of N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide.

9. The preparation method according to claim 1, characterized in that, The imidization process is as follows: sequentially heat treatment at 40~60℃ for 3 h, at 80~100℃ for 2 h, at 120~140℃ for 1 h, and at 160~200℃ for 1 h.

10. The application of the MOFs / polyimide coating according to any one of claims 1 to 4 or the MOFs / polyimide coating prepared by the preparation method according to any one of claims 5 to 9 in the piston skirt of a methanol internal combustion engine.